CITRA BARU VLADIMIR PUTIN DI MEDIA SOSIAL: UPAYA MEMENANGKAN PEMILU PRESIDEN RUSIA 2024 - Nasution, Muhad Alfianda; Elfira, Mina (Multikultura, 2025)
This research analyzes the new image of Vladimir Vladimirovich Putin displayed on social media Instagram @russian_kremlin during the election campaign for the President of the Russian Federation, from 17 February to 14 March, in an effort to win the 2024 Presidential election of the Russian Federation. The method used in this research is qualitative descriptive analysis. The theory used in this research is Roland Barthes (1972) semiotic denotation and connotation. The argument of this research reveals a new image of Vladimir Putin as a leader who is modern, social, understands technology and supports digitalization innovation in Russia.